Study on the interference of vaccine antibodies with the serological diagnosis of leptospirosis in cattle - Martinez, Mara Leila (2024)
A simple IgG-speciﬁc ELISA for Leptospira spp. was compared with the microscopic agglutination test (MAT) to detect IgG antibody responses to a commercial vaccine in cattle. We used an enzyme-linked immunosorbent assay (ELISA) with sonicated Leptospira interrogans serovar copenhageni M 20. After initial vaccination, specific antibodies against Leptospira spp. were detected in 90% of the animals by IgG-ELISA and 60% by MAT, while after booster, antibodies were detected in 100% and 90% of the animals by IgG-ELISA and MAT, respectively. Both serological MAT and ELISA tests revealed interferences of vaccine antibodies. Disease diagnosis with ELISA and MAT methods should be made two and a half months and four months, respectively, after vaccination to avoid interference of vaccine antibodies. On the other hand, our results suggest that IgG-ELISA may be a useful method to assess the development of IgG antibodies induced by Leptospira vaccine.